PENGARUH MORALITAS DAN AKUNTABILITAS TERHADAP PENCEGAHAN FRAUD PADA PEMERINTAH DESA PADA KECAMATAN MOYO HULU (Jurnal Riset Manajemen dan Akuntansi, 2023)
The amount of village funds needs to be balanced with the government's performance in terms of good financial management. The government's performance can be seen from the financial reports that must be prepared by the village apparatus to be accountable for the financial performance during a certain period. The purpose of this research is to examine the influence of morality and accountability on fraud in 12 villages in the Moyo Hulu sub-district. This research is included in quantitative research with an associative approach. The population in this study is the village apparatus in 12 villages in the Moyo Hulu sub-district. The sampling technique used purposive sampling technique, resulting in a total of 60 respondents. The data source used is primary data collected through questionnaires. In this study, multiple linear regression analysis technique is used for data analysis. The results show that morality and accountability have an influence on fraud prevention in village governments. Based on the coefficient of determination (R-Square) of 0.975, it indicates that the variable of fraud prevention can be measured with the presence of morality and accountability variables at 97.5%.